One-step synthesis and densification of nanostructured TiSi2-SiC composite from mechanically activated (TiC+3Si) powders by high-frequency-induced heated combustion - Shon, In-Jin; Park, Hyun-Kuk; Kim, Hwan-Cheol; Yoon, Jin-Kook; Hong, Kyung-Tae; Ko, In-Yong (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Dense nanostructured TiSi2-SiC Composite was synthesized by high-frequency-induced heated combustion synthesis method within 1 min in one step from TiC and 3Si powders. Simultaneous combustion synthesis and densification were accomplished under the combined effects of an induced current and mechanical pressure. Highly dense TiSi2-SiC with relative density of up to 99% was produced under the simultaneous application of a 60 MPa pressure and the induced current. The mechanical properties of the composite were investigated. (c) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: PRESSURE-ASSISTED COMBUSTION; CO HARD MATERIALS; FRACTURE-TOUGHNESS; OXIDATION; MICROSTRUCTURE; INSITU; TI5SI3; MOSI2; WSI2; WC